Reading and Writing Instruction in the Twenty-First Century : Recovering and Transforming the Pedagogy of Robert Scholes - Scholes, Robert, 1929-2016 (Book collections on Project MUSE., 2021)
"Contemporary scholars explore and extend the continued relevance of Robert Scholes's work in English and writing studies. Scholes passed in 2016, leaving a legacy focused on textuality and had significant impact on a range of fields, including literary studies, composition and rhetoric, education, media studies, and digital humanities"--